”– Kuka … puhhuu …? stönade Esaias.Vem pratar?” Litterär flerspråkighet och språkväxling i Mikael Niemis roman Mannen som dog som en lax - Landqvist, Hans (Insitutionen för svenska språket, Göteborgs universitet, 2012)
In this report, I present a study of literary multilingualism and literary code switching (‘LCS’) based on Mikael Niemi’s novel Mannen som dog som en lax (2006) [‘The man who died like a salmon’]. The novel, which has not been translated to English, is set mainly in Tornedalen, a widely bilingual area in Sweden where many people speak both Meänkieli (a recognized minority language, formerly called ‘Tornedal Finnish’) and Swedish. The sender does not consider himself bilingual and most of the intended recipients are not either, even though linguistic conditions are central to the theme of the novel. Swedish is the main language of the novel, while elements of Meänkieli/Finnish and other languages represent a small fraction of the full text. Implicit LCS implicitly dominates in the material through metalinguistic commentaries and contextual clues. The most common type of explicit LCS is, by far, Swedish > Meänkieli/Finnish. Explicit LCS is for the most part emphasized, usually with italics and/or translation to Swedish, and occurs primarily in dialogue. Syntactic integration is more common, while morphological integration of evidence of explicit LCS in the main language of Swedish is unusual. The novel contains examples of LCS used in attempts to reproduce authentic usage and depict an authentic linguistic setting. In other examples, Tornedalen, the Tornedalians, and Meänkieli/Finnish are depicted more as exotic phenomena compared to the majority society. Likewise, there are examples of how readers, depending on their knowledge of Tornedalen, life in the region, and Meänkieli/Finnish, may be included in or excluded from different passages in the novel. Key words: literary multilingualism, literary code switching, Tornedalian literature, Mikael Niemi, Mannen som dog som en lax, Meänkieli, literary stylistics, text studies I den här rapporten redovisas en fallstudie av litterär flerspråkighet och språkväxling utifrån Mikael Niemis roman Mannen som dog som en lax (2006). Romanen utspelar sig huvudsakligen i ...